2012
DOI: 10.1097/mbc.0b013e3283540c0f
|View full text |Cite
|
Sign up to set email alerts
|

Composition of fibrin glues significantly influences axial vascularization and degradation in isolation chamber model

Abstract: In this study, different fibrin sealants with varying concentrations of the fibrin components were evaluated in terms of matrix degradation and vascularization in the arteriovenous loop (AVL) model of the rat. An AVL was placed in a Teflon isolation chamber filled with 500 μl fibrin gel. The matrix was composed of commercially available fibrin gels, namely Beriplast (Behring GmbH, Marburg, Germany) (group A), Evicel (Omrix Biopharmaceuticals S.A., Somerville, New Jersey, USA) (group B), Tisseel VH S/D (Baxter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Using an isolation chamber model of an arteriovenous loop, it was reported that levels of fibrinogen in fibrin sealant have a significant effect on the amount of matrix degradation and vascular in growth [110]. Lower levels of fibrinogen (20 mg/mL as compared to ≥80 mg/mL) appear to increase matrix degradation ( P < 0.05) and increase the amount of vascularized connective tissue ( P < 0.05) present.…”
Section: Fibrin Sealant Laboratory Literaturementioning
confidence: 99%
“…Using an isolation chamber model of an arteriovenous loop, it was reported that levels of fibrinogen in fibrin sealant have a significant effect on the amount of matrix degradation and vascular in growth [110]. Lower levels of fibrinogen (20 mg/mL as compared to ≥80 mg/mL) appear to increase matrix degradation ( P < 0.05) and increase the amount of vascularized connective tissue ( P < 0.05) present.…”
Section: Fibrin Sealant Laboratory Literaturementioning
confidence: 99%
“…26,27 Previous studies have shown that fibrinogen concentration mainly determines the degradation of the fibrin gel part of the matrix and also affects the replacement with vascularized connective tissue. 28 We used a low, but well-studied, fibrinogen concentration of 10 mL/mg in this study to achieve a fast vascularization of the scaffolds. The polymerization time of the fibrin gel highly depends on the thrombin concentration.…”
mentioning
confidence: 99%
“…In addition, it is absorbable and supports angiogenic ingrowth. 55,56 In this study, soaking the scaffolds with fibrin resulted in inferior results when compared with autologous serum and cell culture medium, possibly due to the special nanostructured architecture. Comparison of the two combination groups with expanded MSC and rhBMP-2 in fibrin and serum demonstrated that fibrin is not crucial for the delivery of the growth factor BMP-2 over time.…”
Section: New Bone Formation Depending On Implanted Cells and Carrier mentioning
confidence: 73%